Bioimpedance Spectra Confirm Breast Cancer Cell Secretome Induces Early Changes in the Cytoskeleton and Migration of Mesenchymal Stem Cells - Ana Laura Sánchez-Corrales; César Antonio González-Díaz; Claudia Camelia Calzada-Mendoza; Jesús Arrieta-Valencia; María Elena Sánchez-Mendoza; Juan Luis Amaya-Espinoza; Gisela Gutiérrez-Iglesias (Applied Sciences)
Mesenchymal stem cell (MSC) treatments take advantage of the ability of these cells to migrate to target sites, although they have been shown to move in response to tumor influence. Currently, tools are being developed to detect these opportune changes in cellular behavior patterns. No reports of such changes in the morphological patterns or migration of MSCs in the presence of a tumor environment, which would provide information of high diagnostic value, have been made. We determined the changes in the cytoskeleton and migration of MSCs exposed to the secretome of breast tumor cells via bioimpedance records. MSCs were cultured and incubated in the presence of 24 and 48 h secretomes of the MCF-7 tumor cell line. The proliferation, migration, morphology, cytoskeleton, and electrical bioimpedance were evaluated at 48 h for cells treated with 24 and 48 h secretomes. Secretomes induced early morphological changes related to the migration of MSCs, directly confirmed via bioimpedance, but no changes in cell proliferation were found. These changes cannot be related to a transformation or malignancy phenotype. The modification of the bioimpedance patterns recorded from the first hours suggests that this method can be applied in an innovative way to detect early changes in a cellular population in the clinical diagnostic setting.